2018
DOI: 10.1111/lam.13044
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofVibriosp. in pure cultures and mussel homogenates using high hydrostatic pressure

Abstract: High hydrostatic pressure (HHP) has been applied to inactivate spoilage and pathogenic micro-organisms in a variety of food products, including seafood. Vibrio sp. are frequently reported as the main cause of foodborne illness associated with consumption of raw or undercooked seafood particularly shellfish worldwide. To date, data on the inactivation of Vibrio sp. via HHP are still limited and most of the trials only investigated HHP application in oysters and clams. This study demonstrates the efficacy of HHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…V. vulnificus proved to be more pressure sensitive compared to V. parahaemolyticus (Koo et al., 2006 ; Vu et al., 2018 ; Ye et al., 2012 , 2013 ). Using inoculated oysters, 276 MPa applied for 5 min reduced V. vulnificus by > 5.4 logs, while less than 4 logs were achieved on V. parahaemolyticus (Koo et al., 2006 ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…V. vulnificus proved to be more pressure sensitive compared to V. parahaemolyticus (Koo et al., 2006 ; Vu et al., 2018 ; Ye et al., 2012 , 2013 ). Using inoculated oysters, 276 MPa applied for 5 min reduced V. vulnificus by > 5.4 logs, while less than 4 logs were achieved on V. parahaemolyticus (Koo et al., 2006 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Vu et al. ( 2018 ) concluded that V. vulnificus was the most pressure sensitive among the four Vibrio species tested (i.e. V. vulnificus , V. alginolyticus , V. cholerae and V. parahaemolyticus ); a > 5 log reduction in mussel homogenates is achieved using (i) 350–450 MPa for ≥ 1 min at 25°C for both V. alginolyticus and V. cholerae , (ii) 250 MPa for ≥ 3 min or 350–450 MPa for ≥ 1 min for V. vulnificus and (iii) 350 MPa for ≥ 3 min or 450 MPa for ≥ 1 min for V. parahaemolyticus .…”
Section: Assessmentmentioning
confidence: 99%
“…Several companies have taken advantage of the effortless pressure‐assisted meat extraction using a semiautomatic HPP system to collect the meat (Cao et al., 2017; Xuan et al., 2018). The highly valuable end product can be used for developing some value‐added dishes or be used as minced meat for soups or fillings (Martínez‐Maldonado et al., 2017; 2020; Vu et al., 2018). HPP has been used for opening the shells of crustaceans.…”
Section: Consumer Acceptance Market Trends and Industrial Challengesmentioning
confidence: 99%
“…Inactivation of different Vibrio species on mussel homogenates was evaluated by different HPP (250,350 & 450 MPa) treatments for 1 and 3 min (Vu et al, 2018). Strong resistance was shown by V. alginolyticus and V. cholerae at pressure below 350 MPa.…”
Section: Microbiologymentioning
confidence: 99%
“…V. alginolyticus and V. cholerae required 350-450 MPa for ≥1 min. while V. vulnificus (250 MPa for ≥3 min or 350-450 MPa for ≥1 min) and V. parahaemolyticus (350 MPa for ≥3 min or 450 MPa for ≥1 min) for reducing load by more than 5 log CFU g À1 (Vu et al, 2018). Advantages of two cycles of HPP (600 MPa) for 10 min each could significantly reduce TPC by around 5.7 log CFU g À1 while single treatment at 600 MPa could reduce TPC by around 3.7 log CFU g À1 in minimally processed squids stored for 10 days, proving efficiency of double HPP treatment (Zhang et al, 2015).…”
Section: Microbiologymentioning
confidence: 99%